DEVELOPMENT AND VALIDATION OF AN ANALYTICAL METHOD FOR THE DETERMINATION OF ETHYLENE GLYCOL AND DIETHYLENE GLYCOL IN SYRUP USING GAS CHROMATOGRAPHY-MASS SPECTROMETRY - Andinda Sukma, Fasya
Ethylene glycol and diethylene glycol are two chemicals that can be contained in pharmaceutical dosage form. Exposure that exceeds the acceptable daily intake may cause toxic effects to human. The aim of this research was to obtain a valid analytical method that can be used to determine ethylene glycol and diethylene glycol in syrup dosage form using gas chromatography with a 0.25 mm x 30 m TG-WAXMS column, helium gas with a flow rate of 0.5 mL/min and mass spectrometry detector. The sample was conducted by dilution and extraction methods. The method was validated based on common parameters, including specifications, linearity, precision, and accuracy. Calibration curve of ethylene glycol within a range of 4 - 14 ppm showed a correlation coefficient (r) of 0.997 and diethylene glycol within a range of 8 - 28 ppm showed a correlation coefficient (r) of 0.995. The limits of detection of ethylene glycol and diethylene glycol were 1.299 ppm and 3.435 ppm, respectively, while the limits of quantitation of ethylene glycol and diethylene glycol were 3.170 ppm and 7.626 ppm, respectively. Relative standard deviation of repeatability and intermediate precision of ethylene glycol were 6.145% and 5.989%, respectively. Relative standard deviation of repatability and intermediate precision of diethylene glycol were 5.980% and 6.416%, respectively. The recoveries were in the range of 89.9 - 106.2% for ethylene glycol and 83.5 – 118.0% for diethylene glycol. Based on the results obtained, it can be concluded that the method has been successfully developed and validated hence can be used for determination of ethylene glycol and diethylene glycol in syrup. Levels of ethylene glycol and diethylene glycol in the tested syrups were not more than permitted limit.